2007
DOI: 10.1080/02640410600718640
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making skills and deliberate practice in elite association football referees

Abstract: We examined sport expertise as a function of role. In study 1, referees were better than players in a video-based decision-making task. This provides evidence that there are role-specific skills within one domain or sport. In study 2, we examined the training activities that could be influential in the development of skills in sports officials. Elite association football (soccer) referees retrospectively reported time spent in and perceptions of training activities for three periods: their first year of formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 12 publications
5
106
0
4
Order By: Relevance
“…There are several challenges for sport officials during a match -they must be physically fit (Leicht, 2008), make split-second decisions (MacMahon, Helsen, Starkes, & Weston, 2007), have extensive rule knowledge (MacMahon & Plessner, 2008), communicate with athletes and coaches (MacMahon & Plessner, 2008), and deal with tremendous pressure and scrutiny (Lehman & Reifman, 1987;Nevill, Balmer, & Williams, 2002). Certainly, sport officiating is not an easy avocation.…”
Section: Introductionmentioning
confidence: 99%
“…There are several challenges for sport officials during a match -they must be physically fit (Leicht, 2008), make split-second decisions (MacMahon, Helsen, Starkes, & Weston, 2007), have extensive rule knowledge (MacMahon & Plessner, 2008), communicate with athletes and coaches (MacMahon & Plessner, 2008), and deal with tremendous pressure and scrutiny (Lehman & Reifman, 1987;Nevill, Balmer, & Williams, 2002). Certainly, sport officiating is not an easy avocation.…”
Section: Introductionmentioning
confidence: 99%
“…The number of years as well as the league level contribute to this experience. Evidence suggests that officiating experience determines the performance quality of sports officials (MacMahon, et al, 2007). Using a video-based tackle assessment task, MacMahon, et al (2007) showed that a higher amount of officiating experience correlated with better performance quality of Belgian elite soccer referees.…”
Section: Internal Factors Influencing Judgment and Decision Makingmentioning
confidence: 99%
“…Evidence suggests that officiating experience determines the performance quality of sports officials (MacMahon, et al, 2007). Using a video-based tackle assessment task, MacMahon, et al (2007) showed that a higher amount of officiating experience correlated with better performance quality of Belgian elite soccer referees. Performance quality of sports officials is characterized differently in each sport, although decision or judgment accuracy being the most important aspect.…”
Section: Internal Factors Influencing Judgment and Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations